High rate of non-detectable HIV-1 RNA among antiretroviral drug naïve HIV positive individuals in Nigeria (2013)
Plasma HIV-1 RNA concentration, or viral load, is an indication of the magnitude of virus replication and largely correlates with disease progression in an infected person. It is a very useful guide for initiation of therapy and monitoring of response to antiretro¬viral drugs. Although the majority of patients who are not on antiretroviral therapy (ART) have a high viral load, a small proportion of ART naive patients are known to maintain low levels or even undetectable viral load levels. In this study, we determined the rate of unde-tectable HIV-1 RNA among ART naive HIV positive patients who presented for treatment at the University College Hospital (UCH), Ibadan, Nigeria from 2005 to 2011. Baseline viral load and CD4 lymphocyte cell counts of 14,662 HIV positive drug naive individuals were determined using the Roche Amplicor version 1.5 and Partec easy count kit, respectively. The detection limits of the viral load assay are 400 copies/mL and 750,000 copies/mL for lower and upper levels, respectively. A total of 1,399 of the 14,662 (9.5%) HIV-1 positive drug naive individuals had undetectable viral load during the study period. In addition, the rate of non-detectable viral load increased over the years. The mean CD4 counts among HIV-1 infected individuals with detectable viral load (266 cells/μL; range = 1 to 2,699 cells/μL) was lower than in patients with undetectable viral load (557 cells/μL; range = 1 to 3,102 cells/μL). About 10% of HIV-1 infected persons in our study population had undetectable viral load using the Roche Amplicor version 1.5.